Anxiogenic-like effect of chronic corticosterone in the light-dark emergence task in mice - Ardayfio, Paul; Kim, Kwang-Soo (Behavioral neuroscience, 2006)
Chronic hypercortisolemia is a hallmark of neuroendocrine and psychiatric disorders, such as Cushing's disease and depression. Whether cortisol directly contributes to the altered mood and anxiety symptoms seen in these diseases remains unclear. To address this, the authors have modeled hypercortisolemia by administering corticosterone in the drinking water of female Swiss Webster mice for 17 or 18 days (13 mg/kg). Light-dark emergence, startle habituation, and startle reactivity were measured. Chronic but not acute treatment with corticosterone increased the latency to emerge into the light compartment, an anxiogenic-like effect. Chronic corticosterone treatment did not affect startle habituation, but did reduce startle reactivity. This study suggests that chronic hypercortisolemia may contribute to anxiety-related behavior in patients with Cushing's disease and depression.